2001
DOI: 10.1124/mol.59.2.322
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfonylurea Glimepiride Regulates Intracellular Routing of the Insulin-Receptor Complexes through Their Interaction with Specific Protein Kinase C Isoforms

Abstract: Sulfonylureas may stimulate glucose metabolism by protein kinase C (PKC) activation. Because interaction of insulin receptors with PKC plays an important role in controlling the intracellular sorting of the insulin-receptor complex, we investigated the possibility that the sulfonylurea glimepiride may influence intracellular routing of insulin and its receptor through a mechanism involving PKC, and that changes in these processes may be associated with improved insulin action. Using human hepatoma Hep-G2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In accordance with findings with Hep-G2 cells, this could be attributed to the accelerated recycling of the insulin receptor during its endocytic route and the prevention of insulin-induced receptor down-regulation involving enhanced association of the insulin receptor with the protein kinase C [32]. However, in Hep-G2 cells as well as in skeletal muscles of insulinresistant KK-Ay mice glimepiride did not affect the binding characteristics of the insulin receptor [32,34].…”
Section: The Insulin-sensitizing Activity Of Glimepiride and Its Molesupporting
confidence: 88%
See 2 more Smart Citations
“…In accordance with findings with Hep-G2 cells, this could be attributed to the accelerated recycling of the insulin receptor during its endocytic route and the prevention of insulin-induced receptor down-regulation involving enhanced association of the insulin receptor with the protein kinase C [32]. However, in Hep-G2 cells as well as in skeletal muscles of insulinresistant KK-Ay mice glimepiride did not affect the binding characteristics of the insulin receptor [32,34].…”
Section: The Insulin-sensitizing Activity Of Glimepiride and Its Molesupporting
confidence: 88%
“…The putative insulinsensitizing activity was investigated using glycogen synthesis as parameter. In human hepatoma Hep-G2 cells glimepiride (20 µM) increased glycogen synthesis by 30 to 40% vs. control in the presence of increasing concentrations of insulin, but not in its absence [32]. Similarly, in cultured human myotubes glimepiride (0.1 µM), but not glibenclamide, stimulated the insulin-induced glycogen synthesis by 50 to 70% during 4 h incubation [33].…”
Section: The Insulin-sensitizing Activity Of Glimepiride and Its Molementioning
confidence: 92%
See 1 more Smart Citation
“…Thus, transformed lymphoblasts from subjects with type 2 diabetes mellitus showed impaired intracellular dissociation of insulin-IRK complexes, insulin degradation, and recycling of the IRK when compared with cells from normal subjects, raising the possibility that these defects might underly the insulin resistance seen in these patients (46). Also it has recently been observed that the sulfonylurea glimepiride improved insulin action in hepatoma cells and correspondingly increased the intracellular dissociation of insulin-IRK complexes, the degradation of insulin, and the recycling of internalized IRK in these cells (47). It is tempting to consider that a defect in the vacuolar system responsible for mediating insulin action (endosomes) and insulin processing and secretion (trans Golgi vesicles) may explain both the insulin resistance and impaired ␤ cell function of type 2 diabetes mellitus.…”
Section: Figmentioning
confidence: 99%
“…While direct phosphorylation by PKC does not appear to modulate tyrosine kinase activity (41), an interaction of PKCε with the receptor in liver may affect its ability to phosphorylate its substrates (42). Alternatively, such an association may affect insulin receptor trafficking in hepatocytes (43) and hence both the clearance of insulin by the liver (44) and degradation of the receptor itself (14). …”
Section: Mechanisms Of Pkc-induced Insulin Resistancementioning
confidence: 99%